Marketing of mango in selected barangays of Leon, Iloilo - Durana, Mari Shella Gotico .; Ganadillo, Marcelino Ambong, Jr. (1998.)
This study is an economic analysis of the marketing of mango in selected barangays in Leon. Specifically, this was undertaken, firstly to determine the marketing practices that were employed by both producers and middlemen, secondly, to estimate the marketing margins and costs, thirdly to determine the pricing efficiency, and lastly to identify the different problems in the marketing of the product., Results of the study showed that the producer-respondents preferred wholesalers as their outlet because they offered the producers higher prices as compared to other middlemen. Normally, picked-up was the method selling and installment basis was the terms of payment being widely practiced by almost all of the respondents. The average farm gate was P16.89 per kilo. Kilo was the unit of measurement used. Picking, grading, weighing, and transporting were the different marketing functions by the producers that were identified. Several problems were also determined and the most common one was the low price of the product. As for the middlemen-respondents, the minimum buying price of the mango was P13.00 per kilo and the lowest selling price was P19.00 per kilo while the highest was P26.00 per kilo. The gross margin and financial net margin was P6.11 per kilo. The total labor cost was P0.33 per kilo. Marketing functions were identified and these were weighing, packaging, grading, loading, and unloading. Distance was the number one problem of the middlemen that was determined. Several policy recommendations were also mentioned so as to improve the mango industry in Leon. One of the recommendations mentioned was that the cooperatives should provide other functions aside from marketing alone. Second, is that the cooperatives should be a ready market for the producers so as to increase the share of the farmers in the total marketing bill. Third, is that there should be improvement in the infrastructure facilities so as to lessen the transportation cost incurred by the farmers. Fourth, there should be a good marketing information system so as to appreciate the good marketing system. Lastly, the government should support services to cooperatives. Other researchers who wish to do similar research on this field is also encouraged.
Research Project (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas.
Keywords: Mango -- Leon, Iloilo